Austenitic TRIP/TWIP Steels and Steel-Zirconia Composites : Design of Tough, Transformation-Strengthened Composites and Structures - Biermann, Horst; Aneziris, Christos G.; Biermann, Horst; Aneziris, Christos G. (Springer Nature, 2020)
This open access book presents a collection of the most up-to-date research results in the field of steel development with a focus on pioneering alloy concepts that result in previously unattainable materials properties. Specifically, it gives a detailed overview of the marriage of high-performance steels of the highest strength and form-ability with damage-tolerant zirconia ceramics by innovative manufacturing technologies, thereby yielding a new class of high-performance composite materials. This book describes how new high-alloy stainless TRIP/TWIP steels (TRIP: TRansformation-Induced Plasticity, TWIP: TWinning-induced Plasticity) are combined with zirconium dioxide ceramics in powder metallurgical routes and via melt infiltration to form novel TRIP-matrix composites. This work also provides a timely perspective on new compact and damage-tolerant composite materials, filigree light-weight structures as well as gradient materials, and a close understanding of the mechanisms of the phase transformations. With a detailed application analysis of state-of-the-art methods in spatial and temporal high-resolution structural analysis, in combination with advanced simulation and modelling, this edited volume is ideal for researchers and engineers working in modern steel development, as well as for graduate students of metallurgy and materials science and engineering.
English
Keywords: Materials science; Metals technology / metallurgy; Ceramics & glass technology; Mathematical modelling; Structural Materials; Metallic Materials; Ceramics, Glass, Composites, Natural Materials; Materials Engineering; Mathematical Modeling and Industrial Mathematics; Metals and Alloys; Ceramics; Steel-Matrix Composite; Austenitic Stainless Steels; Powder Metallurgy; Fracture Toughness; Mechanical Modeling; Melt Flow Behavior; CrMnNi Steels; Ceramic Casting; Melt Infiltration; Open Access; Materials science; Structural engineering; Metals technology / metallurgy; Industrial chemistry & chemical engineering; Mathematical modelling; Maths for engineers